The Evaluation of Innovative PUSPAGA KENARI Program for Child Marriage Prevention in Yogyakarta City - Fitri, Nabila; Setyani, Enrika; Mahiroh, Hodimatum; Rahmatika, Nanda (BKM Public Health and Community Medicine, 2024)
Background: Child marriage, a marriage with one or both premarital couple under 18 years old. The number of child marriages in Yogyakarta increase from 46 couples (2021) to 61 couples (2022). Despite its implications not only on education and employment level, but also on the risk of giving birth a stunting child or even the risk of maternal death. The government of Yogyakarta collaborated with DP3AP2KB implemented Pusat Pembelajaran Keluarga (PUSPAGA) program named KENARI (Keluarga Ngayomi Asah Asih Asuh Harmonis) to prevent child marriage. Purpose: This study aims to evaluate the innovation program of PUSPAGA KENARI in Yogyakarta City Method: A document review was conducted on May 2024 used data sourced from DP3AP2KB Office, PUSPAGA KENARI social media accounts, and website news page. Result: PUSPAGA KENARI has various innovations according to its access, coverage, and frequency of program implementation. Besides being headquartered in a strategic area, PUSPAGA’s services could be accessed online through Sila Eling on Jogja Smart Service application, linktree on its Instagram account, and Telepon Sahabat Anak (TeSa). The counselling services which collaborate with psychologist from 18 Puskesmas are free and open to the target group of families, parents, premarital couple, and children. There are also innovations in PAAR EDI (Pola Asuh Anak dan Remaja di Era), PUSPAGA smart online course, and parenting talk shows on local television. The program used culture-based approach and integrated with existing program such as Sekolah Ramah Anak in program implementation. Education by IG Live conducted regularly on Monday and Thursday while other services can be accessed online and offline from Monday to Friday at 8am – 3pm Conclusion: PUSPAGA KENARI has good program innovations to reach various target groups in preventing child marriage in the city of Yogyakarta. The best practice of program innovations can be adopted to other districts/cities in implementing PUSPAGA.